Enhancing Independence in Activities of Daily Living, Cognitive, and Physical Skills for Elderly with Dementia: A Randomized Controlled Trial of Meaningful Task-Oriented Intervention - Farzad Rabiei; Malahat Akbarfahimi; Mahtab Roohi-Azizi; Marjan Ghandi (Shiraz University of Medical Sciences, 2024)
Background: Dementia is recognized as a neurodegenerative disease that gradually causes serious cognitive, motor, and functional impairments in affected individuals. This study explored the impact of a meaningful task-oriented intervention on independence in activities of daily living, cognitive status, and physical abilities, including gait speed and balance, among elderly patients diagnosed with mild to moderate dementia. Methods: In this randomized controlled trial, 40 participants aged 60-70, with a Functional Assessment Staging Tool (FAST Scale) score of 1-5, were recruited. They were randomly assigned to either a control group (n=20) receiving standard care, including medication and routine consultation, or an intervention group (n=20) receiving standard care along with eight 45-60-minute sessions of task-oriented interventions. These interventions were centered around familiar daily life activities in the home environment and were conducted twice a week. The primary outcome measure was the participants' independence in activities of daily living, assessed using the Barthel Index. Secondary outcome measures included cognitive function, evaluated using Addenbrooke's Cognitive Examination-Revised, and physical performance, assessed through the Timed Up and Go test, 10 Meter Walk Test, and Berg Balance Scale. Results: The meaningful task-oriented intervention demonstrated significant improvements in independence in activities of daily living (p<0.01) compared to the control group. Additionally, improvements were observed in cognitive function and physical performance, including balance, lower limb strength, and walking speed (p<0.05). Conclusion: The integration of meaningful task-oriented interventions centered around familiar activities within the home environment appears to offer significant benefits for elderly patients with dementia. By engaging in tasks that resonate with their daily routines, these interventions can support the maintenance of essential skills and foster a sense of independence among affected individuals.